Assessment of Mercury-Polluted Soils Adjacent to an Old Mercury-Fulminate Production Plant - M. Camps Arbestain; L. Rodríguez-Lado; M. Bao; F. Macías (Applied and Environmental Soil Science)
Mercury contamination of soils and vegetation close to an abandoned Hg-fulminate production plant was investigated. Maximum concentrations of Hg (>6.5 g kg−1 soil) were found in the soils located in the area where the wastewater produced during the washing procedures carried out at the production plant used to be discharged. A few meters away from the discharge area, Hg concentrations decreased to levels ranging between 1 and 5 g kg−1, whereas about 0.5 ha of the surrounding soil to the NE (following the dominant surface flow direction) contained between 0.1 and 1 g kg−1. Mercury contamination of soils was attributed (in addition to spills from Hg containers) to (i) Hg volatilization with subsequent condensation in cooler areas of the production plant and in the surrounding forest stands, and (ii) movement of water either by lateral subsurface flow through the contaminated soils or by heavy runoff to surface waters.